PERSPEKTIF SOSIOLOGIS TERHADAP TOLERANSI ANTAR UMAT BERAGAMA DI KOTA SINGKAWANG - Sri Sudono Sudono Saliro (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
The purpose of this study is to analyze the religious tolerance among different communities in the city of Singkawang. It focuses on the forms of the tolerance as well as the supporting and challenging factors toward tolerance among religious people in the city. This is an empirical research in which it employs descriptive qualitative methods that were used to obtain data through observation and interviews. Among the results of the field research is a finding that in Singkawang City, inter-religious relationships have been facilitated by collaborated forums namely FKUB (Forum Komunikasi Umat Beragama) and FKPELA (Forum Komunikasi Pemuda Lintas Agama). Special for FKPELA, this forum has been claimed as the only interfaith youth communication forums found in Indonesia. Among the supporting factors for the interfaith cooperations are the emotional ties and environmental condition. In this context, the community grows and develops in an environment surrounded by people of different religions. Regarding the challenging factors, it was found that the socio-political situation and traumatic memory of conflict in the city’s history could constitute as inhibiting factors.